The law and practice of international banking : banking law Volume 2 - Penn, G.A.; Shea, A.M.; Arora, A. (London : Sweet & Maxwell, 1987)
This new work was originally conceived as being intended for degree and post-graduate students and for practitioners who regularly find themselves engaged in this complex area of law.
Includes bibliographical footnotes and index.
rpm 25/01/2019
Loans
Keywords: Banks and banking, International